Appropriation, Creolization or Entanglement?: Jewish Religious Architecture in Cologne 1060–1170 - Bodner, Neta (Frühmittelalterliche Studien, 2025)
This article examines the applicability of three theoretical models - cultural appropriation, entanglement, and creolization - for understanding Jewish religious architecture in medieval Cologne in relation to contemporary Christian architecture in the same city. Focusing on the synagogue and mikveh constructed from the eleventh to the thirteenth centuries, it argues that these Jewish structures reveal underlying similarities despite being visually distinct from concurrent Christian buildings. Looking at shared technologies, resources, infrastructures, attitudes to ritual, and design aspirations confirms the underlying overlaps between these distinct architectural cultures. By favoring creolization as a model, the article illuminates how both rivalry and cooperation, adoption, and rejection underpinned by profound power imbalances influenced Cologne’s Jewish architecture in the Middle Ages.